Registered counsellors’ experiences with managing ethical issues - Chilwane, Kgothatso Cyril (Rhodes University, 2026)
Ethical issues are an intrinsic part of counselling practice, yet there is limited empirical research examining how South African Registered Counsellors (RCs) navigate such complexities. While ethical principles are covered during formal training, there appears to be a disconnect between theoretical instruction and the realities of ethical decision-making in practice. The challenges faced often involve reconciling professional standards with client needs, navigating power dynamics in therapeutic relationships, and interpreting ethical obligations within broader legal and institutional frameworks. This study responds to the gap in research and training by exploring the lived experiences of RCs in managing ethical issues. Drawing on a qualitative design, five purposively selected RCs participated in semi-structured interviews. Thematic analysis, underpinned by a social constructionist framework, was used to identify patterns in their narratives. The findings reveal that RCs frequently encounter ethical tensions related to confidentiality, boundary-setting, and the limits of client autonomy, particularly when working with vulnerable groups. Moreover, participants expressed that their academic training often lacked the practical application of ethics, leaving them underprepared for the nuanced decisions required in the field. These insights underscore the need for enhanced ethics education that bridges the gap between theory and practical application. The study contributes to the literature by highlighting the specific ethical challenges encountered by RCs and offers recommendations for curriculum reform and professional development aimed at strengthening ethical competence in counselling practice.
Keywords: Counselors (http://id.loc.gov/authorities/subjects/sh85033428); Decision making (http://id.loc.gov/authorities/subjects/sh85036199); Health Professions Council of South Africa (http://id.loc.gov/authorities/names/n2001130317); Counselling Psychology; Ethical dilemma (https://www.wikidata.org/wiki/Q192568); Decision-making models (https://www.wikidata.org/wiki/Q5249202)